Charge carrier density noise in graphene: effect of localized/delocalized traps. (10th September 2019) - Pellegrino, Francesco M D; Falci, Giuseppe; Paladino, Elisabetta
Abstract: Graphene-based devices show 1/ f low-frequency noise in several electronic transport properties, such as mobility and charge carrier concentration. The recent outburst of experimental studies on graphene-based devices integrated into circuit quantum electrodynamics systems has rekindled the interest in low frequency charge noise. We investigate charge carrier density noise in graphene within the McWorther model where noise is induced by electron traps in the substrate. We focus on the large doping regime and introduce a simple modelization of the effect of localized/delocalized traps in terms of single/double spin occupancy of trap states. We find that in both cases the charge carrier spectrum of graphene obeys the power-law behavior where is very close to the unity, and for each case we evaluate the deviation . The amplitude of the noise is found to depend on the trap energy distribution and on temperature. Single/double spin occupancy of trap states influences the temperature dependence of noise amplitude only to second order.